Strategi Pemasaran Wisata Olahraga untuk Meningkatkan Pertumbuhan Ekonomi Masyarakat di Hutan Lindung Kota Langsa: Studi Survei - Yoki Afriandy Rangkuti; Julio Roberto; Wina Fitria Sari; Wahyu Suganda; Yoga Oskar Zebua; Yesaya Ginting (Program Studi Pendidikan Jasmani Kesehatan dan Rekreasi, 2024)
Protected forest is an area on the equator and is one of the tropical forests full of benefits. One of the tourism strategies intended for this tourist spot is to build recreational sports facilities and infrastructure to increase the number of visitors. However, the most popular attractions among visitors, which also have the potential to absorb a significant amount of labor from the local community, have not yet been actively utilized. The goal to be achieved is to assess the readiness and safety of recreational sports facilities in the protected forest of Langsa City in fostering economic growth for the surrounding community. This research uses a quantitative approach and employs survey research. The sample in this study includes all recreational sports facilities and infrastructure. Data collection techniques used in this study include observation, interviews, documentation, and the classification of recreational sports in the Langsa City Protection Forest. The results show that almost all recreational sports facilities and infrastructure are in good condition and suitable for use. However, the findings indicate that: 1) PT. PEKOLA has not implemented an effective recreational sports marketing strategy to attract a large number of visitors from outside the region, 2) there are no active human resources managing the recreational sports, and 3) the local community has not yet experienced economic growth as a result of this tourist attraction.